2010
DOI: 10.1242/jeb.037101
|View full text |Cite|
|
Sign up to set email alerts
|

Oxidative stress and the effect of parasites on a carotenoid-based ornament

Abstract: It has been drawn to our attention that Fig. 1A,C,D in J. Exp. Biol. 213, 400-407 appears to show the same data as fig 1a,d,e in a paper published by (some of) the same authors in Journal of Evolutionary Biology (Mougeot et al., 2010). The authors wish to clarify the relationship between these two papers and rectify the lack of cross-referencing.Both papers focus on red grouse and are outputs from the same large-scale field manipulation undertaken in 2006. They represent two, very different, stand-alone studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 64 publications
2
28
0
Order By: Relevance
“…2010), but instead in testosterone-dependent immune function, oxidative status or physiological stress (Mougeot & Redpath 2004; Bortolotti et al. 2009; Mougeot et al. 2010a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2010), but instead in testosterone-dependent immune function, oxidative status or physiological stress (Mougeot & Redpath 2004; Bortolotti et al. 2009; Mougeot et al. 2010a).…”
Section: Methodsmentioning
confidence: 99%
“…2004; Mougeot & Redpath 2004; Mougeot 2008), oxidative status (Mougeot et al. 2009, 2010a) or physiological stress (Bortolotti et al. 2009; Mougeot et al.…”
Section: Introductionmentioning
confidence: 99%
“…redness and yellowness), and haemoglobin and melanin homogeneity impact perceptions of health and attractiveness across multiple face ethnicities [26,62]. Additionally, skin colour may inform carotenoid concentration, which may reflect resistance to infectious disease and oxidative damage [63], though there is currently little direct support for the idea that carotenoid concentration in human skin reflects adaptation to advertise robustness in the way that concentrations of carotenoids in colourful bird feathers may do [64]. Indeed, at the current time, little direct evidence addresses whether skin tone or colour reflects current infection levels or infectability.…”
Section: Preferences For Health In Humansmentioning
confidence: 99%
“…This holds true for both feather ornaments (McGraw and Hill 2000;Hõrak et al 2004) and living tissues such as the ramphotheca of the bill or bare skin (Pérez- Rodríguez and Viñuela 2008;Mougeot et al 2010). In our previous experiments, we have shown that redness of the grey partridge eye patch is caused by carotenoid pigmentation (Svobodová et al 2013), similarly to several other galliform species expressing red-coloured skin-based ornamentation (e.g., Egeland et al 1993;Mougeot et al 2007).…”
Section: Discussionmentioning
confidence: 98%